The centrality of work in the United States of America. A transversal exploration: 1995–2014 - Mejía Reyes, Carlos; Martín Artiles, Antonio (Sociedad y Economía, 2018)
Western capitalist societies have ideologically defined work as the generating activity of individual and collec- tive material support, that forms the basis of social cohesion and that provides virtue to the subjects. However, in the contemporary context its importance tends to diminish due to the transformations in the productive processes and the prevailing precarious conditions of employment. Thus, the objective of this paper is to ex- pose the statistical performance of work centrality in the United States of America, through the World Values Survey, in the surveys from 1995 to 2014, by means of transversal or prevalence analysis, with regard to basic sociodemographic variables. With the above, a general overview is offered and emphasis is placed on the latest wave, to highlight and explain the tendency towards the low value of work.